Advances in Treatment of Hepatitis C and B 2017
DOI: 10.5772/67149
|View full text |Cite
|
Sign up to set email alerts
|

HCV Treatment Failure in the Era of DAAs

Abstract: Hepatitis C virus (HCV) has six well-known genotypes in worldwide and has a very high genetic diversity. Introduction of DAAs leads to improvement of treatment results with SVR rates exceeding 95%. Development of HCV treatment resistance is a problematic issue that needs sufficient solutions. Many hosts, viral, and drug factors are implemented in the process of treatment resistance. Lack of clinical trials on treatment failure leads to lag in development of certain consensuses for retreatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…On the other hand, none of the baseline factors showed significant association with treatment failure in the subgroup of patients with severe renal impairment except for serum bilirubin. Some clinical trials on DAAs showed mildly better response in treatment naive patients than those who previously failed treatment with Peg‐IFN‐RBV . Advanced fibrosis stage also affects the response rates to DAAs with a wide variable SVR results in cirrhotic patients ranging between 33% and 100% SVR rates …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, none of the baseline factors showed significant association with treatment failure in the subgroup of patients with severe renal impairment except for serum bilirubin. Some clinical trials on DAAs showed mildly better response in treatment naive patients than those who previously failed treatment with Peg‐IFN‐RBV . Advanced fibrosis stage also affects the response rates to DAAs with a wide variable SVR results in cirrhotic patients ranging between 33% and 100% SVR rates …”
Section: Discussionmentioning
confidence: 99%
“…The most major factor leading to treatment failure is the development of viral resistance. Although this incident is rather rare, it nonetheless presents a difficult scenario [7,8] .…”
Section: Hcv Treatment Failurementioning
confidence: 94%
“…Терапия ПППД демонстрирует устойчивый вирусологический ответ, в среднем >90 %, по сравнению с 40-50 % устойчивого вирусологического ответа при использовании интерферона и рибавирина при инфекции ВГС генотипов 1 и 4, 60-70 % при генотипах 5 и 6 и 80-90 % при генотипах 2 и 3. Доступность терапии ПППД расширяет возможность излечения от хронического гепатита С (ХГС) для различных групп пациентов, которые в эпоху интерферона не рассматривались для назначения терапии, например, пациенты с заболеваниями печени, аутоиммунными заболеваниями, почечной недостаточностью или пациенты после трансплантации органов [8].…”
Section: Introductionunclassified